THE ROLE OF MEDIA IN SOCIALIZING INDONESIAN LANGUAGE TERMINOLOGY - Dindin Samsudin (Balai Bahasa Jawa Barat, 2015)
FOREIGN language can influence Indonesian language a great deal for the society'sneed of a terms of reference for a symbol. The absence of a proper terms inIndonesian language for certain symbol encourages people to borrow foreignor local words to express their ideas. Such use would then spread out among theIndonesian speakers. To avoid it, Indonesian terminology was compiled butunfortunately it was not known yet by the Indonesian speakers. It resulted in thevast use of foreign words by the people. This article aims at describing the role ofthe media in introducing new words to the society using descriptive qualitativemethod and collecting data via literatur study. It showed that the media had asignificant role in socializing Indonesian terminology.